(untitled) (Web of Teachers: Inderscience Research, 2024)
Today, modern preschool children are actively interested in information and communication technologies, and many of them have already mastered to some extent some of the tasks of the tablet, personal computer, sensory phone and Internet capabilities. Therefore, it is natural that the use of medial tools to stimulate the cognitive interest of preschool children in a particular area of medial education is a potential fruit.